Atypical structure of the nuclear membrane, distribution of nuclear pores and lamin B1 in spermatozoa of patients with complete and partial globozoospermia - Bragina, Elizaveta; Kurchashova, Svetlana; Suhomlinova, Marina; Gasanova, Tatiana; Ermolaeva, Svetlana; Sorokina, Tatyana; Kirs, Eva; Arifulin, Evgeniy; Solovova, Olga; Ryzhkova, Oxana; Khayat, Sabina; Andreeva, Marina; et al. (Frontiers in Genetics, 2024)
Globozoospermia is a form of male infertility characterized by spermatozoa with spherical heads lacking acrosomes. The aim of this study was to evaluate ultrastructural and molecular defects in different types of globozoospermia. Semen samples from 12 infertile patients (9 with complete globozoospermia and 3 with partial globozoospermia) and 10 normozoospermic men (control) were examined by transmission electron microscopy and immunocytochemistry with antibodies against lamin B1. The presence of lamin A and progerin was assessed by reverse transcription-PCR. Whole exome sequencing was performed in three patients. In semen samples with complete and partial globozoospermia, lamin B1 was observed at the periphery of sperm nuclei, whereas lamin A and progerin were absent. Nuclear envelope pores were found in spermatozoa from both patient groups, regardless of morphology and chromatin condensation, in contrast to the control group. Non-condensed chromatin was present in 51-81% of cases of complete globozoospermia and in 36-79% of cases of partial globozoospermia. Homozygous DPY19L2 and SPATA16 variants were identified in two patients with partial globozoospermia and one patient with complete globozoospermia. An atypical nuclear membrane with abnormal nuclear pore distribution and lamin B1 localization was observed in spermatozoa from patients with both complete and partial globozoospermia. The genetic defects in the DPY19L2 and SPATA16 genes detected in patients from both globozoospermic groups suggest a generalized disruption of nuclear structure in globozoospermia, highlighting the genetic and phenotypic similarities between complete and partial globozoospermia.